(untitled) (Revista LIDER, 2020)
Alongside the tradition of social theory, the concept of territory has been widely used but poorly systematized. It is generally employed in an objective sense, namely as a territory which contains social relations and exerts causal efficacy upon the production of the social. On the contrary, from a systemtheoretical point of view, this paper holds the hypothesis that the territory is a conceptual construction produced in the social and temporal dimensions of meaning, which in turn reflects the operation of the factual dimension in terms of positions, distances, and limits. In order to substantiate this hypothesis, anthropological, sociological, and political theories drawing upon the concept of territory are revised, their limitations exposed, and some theoretical elements are extracted from aiming to identify the meaning and function of the territory in modern society.